Reflections on a Career in Marine Geoscience. Issue 1 (17th November 2021) - Watts, A. B.
Abstract: I began my career in the late 1960s at a time when some major oceanographic institutions were running upwards of 30 cruises a year. By the early 1980s, changes in funding patterns, satellite remote sensing, and "law of the sea" had started to impact ocean exploration. Nevertheless, technological advances, especially in sonar and seismic systems, have led to new discoveries on seafloor processes and underlying structures. Today, marine geoscience plays a pivotal role in Earth system science through projects such as Seabed 2030, International Ocean Drilling (IODP), and seismic imaging of mantle lithosphere, each of which pose opportunities and new challenges for the next generation. Plain Language Summary: The marine geosciences are concerned with the geological processes that are occurring on the ocean floor and the structure and tectonic evolution of the crust and mantle that underlie it. The discipline expanded rapidly following technological developments during World War II, especially those in continuously recording echo sounders and towed magnetometers. These instruments provided the critical data sets with which to test the hypotheses of continental drift and seafloor spreading and, eventually, helped lay the framework for the paradigm of plate tectonics. My career began in the late 60s at a time of intense ocean exploration, driven in part by scientific interest in the distribution of deep‐sea sediments, the age of the oceanic crust and the deep structure of mid‐ocean ridges, deep‐sea trenches and fracture zones, and in part by societal interest in deep‐sea mineral resources and the United Nations convention on "law of the sea." Today, the focus is on measuring the changes that are occurring due, for example, to submarine earthquake, landslide and volcanic activity and what they tell us about how our fragile planet is changing, in any event, and independently of externally driven environmental change and human activity. Key Points: Knowledge of core geology is invaluable for defining the problems that can be addressed using geophysical methods It is important to be generous in the mentoring of students and early career scientists, as they are part of a research scientist's legacy There has never been a better time to be a marine geoscientist as we learn how our fragile ocean has changed and might change in the future